The longitudinal directional associations of meaningful work with mental well-being: initial findings from an exploratory investigation - Herr, Raphael; Brokmeier, Luisa Leonie; Baron, Bertil Nestorius; Mauss, Daniel; Fischer, Joachim E. (BMC Psychology, 2023)
An increasing number of studies reveal that more meaning in life is positively related to mental well-being. Meaning in life can be derived from different sources, including the workplace. The aim of this study was to explore the longitudinal directional association of meaningful work with mental well-being. Prospective data from 292 persons at two timepoints (two-week interval) were used to estimate the cross-lagged relationship and directionality of meaningful work with mental well-being. The cross-lagged panel model had a good fit to the data (Chi2 ms(90) = 150.9; p < 0.001; RMSEA = 0.048; p = 0.576; CFI = 0.984; TLI = 0.979; SRMR = 0.040) and showed that levels of meaningful work at t1 had a positive effect on mental well-being at t2 (β = 0.15, p = 0.010). But mental well-being at t1 did not affect meaningful work at t2 (β = 0.02, p = 0.652). Sub-analyses revealed the effects to be mainly driven by women (as opposed to men) and white-collar workers (as opposed to blue-collar workers). This study confirmed a directional association of meaningful work on mental well-being, indicating that more meaningful work has beneficial mental well-being effects.
Gesehen am 10.09.2024